Analysis of Class XII Students' Understanding of Concepts on the Topic of Newton's Laws - Nasution, Juwairiyah Hasana (Al-Khazini: Jurnal Pendidikan Fisika, 2025)
One of the core competencies in physics lessons is that students are expected to have the ability to understand physics concepts, explain the relationship between concepts and apply concepts flexibly, accurately, efficiently and precisely, in solving problems. There are many students who, after studying physics, are unable to understand even the simplest parts, many concepts are understood incorrectly so that physics is considered a difficult, complicated and difficult science. Understanding concepts is the most important part of learning physics, one of which is Newton's Laws. This research was conducted on 21 students at one of the high schools in Medan City, SMAS GAJAH MADA MEDAN using descriptive-quantitative research methods. This research aims to determine the level of understanding of students' physics concepts on the topic of Newton's Laws and to analyze what problems occur to students in learning physics. This research is a quantitative descriptive study using a 15-question two-tier instrument about Newton's Laws. Based on this research, students experienced misconceptions on all sub-topics of Newton's Laws which were tested. Students experienced misconceptions regarding Newton's Law material with an average percentage of incorrect answers, namely 62 .6%.